Indigenous peoples' wisdom and power : affirming our knowledge through narratives - Goduka, Nomalungelo I.; Kunnie, Julian (Ashgate, 2006)
Capturing the narratives of indigenes, this book presents a unique anthology on global Indigenous peoples' wisdoms and ways of knowing. Covering issues of religion, cultural self-determination, philosophy, spirituality, sacred sites, oppression, gender and the suppressed voices of women, the diverse global contexts across Africa, Asia, the Middle East, North and South America, and Oceania are highlighted. The contributions represent heart-felt expressions of Indigenous peoples from various contexts - their triumphs and struggles, their gains and losses, their reflections on the past, present, and future - telling their accounts in their own voices. Opening new vistas for understanding historical ancient knowledge, preserved and practiced by Indigenous people for millennia, this innovative anthology illuminates areas of philosophy, science, medicine, health, architecture, and botany to reveal knowledge suppressed by Western academic studies.